Determination of the quality index of a Paleudult under sunflower culture and different management systems - Fernandes, Jairo Costa [UNESP]; Gamero, Carlos Antonio [UNESP]; Rodrigues, José Guilherme Lança; Mirás-Avalos, José Manuel (Elsevier, 2011)
Soil is an essential resource for life and its properties are susceptible to be modified by tillage systems. The impact of management practices on soil functions can be assessed through a soil quality index. It is interesting to assess soil quality in different soil types. Therefore, the aim of this study was to determine the soil quality index of a Paleudult under different management conditions and sunflower culture. The experiment was carried out in Botucatu (SP, Brazil), in an 11-year non-tilled area used for growing soybean and maize during summer and black oat or triticale in winter. Four management systems were considered: no-tillage with a hoe planter (NTh), no-tillage with a double-disk planter (NTd), reduced tillage (RT) and conventional tillage (CT). Soil samples were taken from the planting lines at harvest time. To determine the soil quality indices, following the methodology proposed by Karlen and Stott (1994), three main soil functions were assessed: soil capacity for root development, water storage capacity of the soil and nutrient supply capacity of the soil. The studied Paleudult was considered a soil with good quality under all the observed management systems. However, the soil quality indices varied between treatments being 0.64, 0.68, 0.86 and 0.79 under NTh, NTd, RT and CT, respectively. Physical attributes such as resistance to penetration and macroporosity increased the soil quality index in RT and CT compared to NTh and NTd. The soil quality indices obtained suggested that the evaluated soil is adequate for sunflower production under our study conditions. In view of the SQI values, RT is the most suitable management for this site since it preserves soil quality and provides an acceptable sunflower yield. © 2011 Elsevier B.V.
Keywords: Indicators of soil quality; Soil health; Soil productivity; Sustainability; Yield; Soil quality; Agricultural machinery; Agriculture; Fish; Management; Productivity; Quality assurance; Rating; Sustainable development; Soils; crop yield; dicotyledon; macropore; maize; soil nutrient; soil quality; soil type; soybean; tillage; water storage; Botucatu; Brazil; Sao Paulo [Brazil]; Avena strigosa; Glycine max; Helianthus; Triticosecale; Zea mays